Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fimmu.2022.859964
|View full text |Cite
|
Sign up to set email alerts
|

Computational Structure Prediction for Antibody-Antigen Complexes From Hydrogen-Deuterium Exchange Mass Spectrometry: Challenges and Outlook

Abstract: Although computational structure prediction has had great successes in recent years, it regularly fails to predict the interactions of large protein complexes with residue-level accuracy, or even the correct orientation of the protein partners. The performance of computational docking can be notably enhanced by incorporating experimental data from structural biology techniques. A rapid method to probe protein-protein interactions is hydrogen-deuterium exchange mass spectrometry (HDX-MS). HDX-MS has been increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…However, its accuracy and precision can be compromised by insufficient peptide coverage for large complexes or highly glycosylated antigens, or the inability to discriminate between direct binding interface and allosteric conformational change. 32 The Ala mutagenesis technique can provide some answers on the areas of the antigen involved in the interaction, but is far less precise than DMS, which scans the 20 proteinogenic amino acids. In our dataset, we observe that Ala substitutions would not have identified some important positions, such as K151 for mAb B or L310 for mAb A, and of course not A108, which is already an alanine residue.…”
Section: Discussionmentioning
confidence: 99%
“…However, its accuracy and precision can be compromised by insufficient peptide coverage for large complexes or highly glycosylated antigens, or the inability to discriminate between direct binding interface and allosteric conformational change. 32 The Ala mutagenesis technique can provide some answers on the areas of the antigen involved in the interaction, but is far less precise than DMS, which scans the 20 proteinogenic amino acids. In our dataset, we observe that Ala substitutions would not have identified some important positions, such as K151 for mAb B or L310 for mAb A, and of course not A108, which is already an alanine residue.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing crosslinking distances and contacting residues guided their docking experiment to afford the best scoring complex that recapitulates overall HDX-MS results. We should mention that HDX-MS for docking studies in epitope mapping is not new (Pandit et al, 2012) and is summarized in (Tran et al, 2022) 7 Conclusion and future prospects Meta analysis of >80 papers reviewed (Supplementary Table S1) in the preparation of this article indicates interesting trends for HDX-MS in epitope mapping (Figure 9). 1) Immobilized pepsin columns now enjoy widespread popularity in the field.…”
Section: Combining Hdx-etd-ms Crosslinking and Dockingmentioning
confidence: 94%
“…Previous studies [127][128][129][130][131][132] demonstrated that sophisticated sampling methods (such as MD simulations) are needed to match structures to the experimental HDX data, as well as to better understand the factors influencing the HD exchange. HDX data measured from MS have also been used for computational structure prediction [133] and for protein-protein docking [134,135].…”
Section: Hydrogen-deuterium Exchange (Hdx)mentioning
confidence: 99%